Embankment stabilisation using lime and ash: an option for safer slopes - Kassim, Khairul Anuar (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 1999)
One of the low-cost techniques of preventing the slope failure is to stabilise the freshly built slope using lime piles or lime columns. This may involve some extra costs . on the. project but in the-long run maintenance cost may be reduced sign ificantly. A new technique of construc ting a stable embankment is introduced using strips of stabi lised layers. A combination of laboratory tests on control specimens and sui table design procedures allow the effectiveness of the stabilised embankment to be assessed